Impact of elevated cytosolic and apoplastic invertase activity on carbon metabolism during potato tuber development - Sonnewald, Uwe; et al. (OXFORD UNIV PRESS, 2000)
During tuberization in Solanum tuberosum var. Desiree maximal catalytic activities of invertase(s) and sucrose synthase are inversely correlated. During the early stages, invertase activity is high and declines during maturation. The decrease in invertase activity is accompanied by a decrease in the hexose to sucrose ratio and an increase in sucrose synthase activity. This switch is paralleled by the onset of the storage phase as shown by the accumulation of starch and storage proteins. Biochemical and genetic evidence suggests that sucrose synthase activity is positively correlated with sink strength. To explore the possibility of enhancing sink strength in potato tubers by elevating the sucrolytic capacity, transgenic potato plants expressing either cytosolic or apoplastic yeast invertase in their tubers were made. Surprisingly, cytosolic invertase led to a decrease and apoplastic invertase to an increase in tuber yield. To understand the causes of the observed phenotypes, carbon metabolism in tubers of transgenic and control plants was analysed during different stages of tuber development. Both cytosolic and apoplastic invertase resulted in decreased sucrose and elevated glucose contents, indicating that sucrose is accessible in both compartments. Metabolic perturbation, however, was found to be compartment specific. Elevated cytosolic invertase activity led to increased carbon flux towards glycolysis and accumulation of phosphorylated intermediates. The phosphorylated intermediates were not used to build up starch, In contrast, apoplastic invertase does not lead to a significant increase in hexose phosphates compared to untransformed controls. Thus, hexoses originating in the apoplast are not efficiently phosphorylated during potato tuber development, which might be explained by an endocytotic uptake of sucrose and/or hexoses from the apoplast into the vacuole bypassing the cytosolic compartment.
Keywords: potato tuber; invertase; development; carbon metabolism; Solanum tuberosum